CILOR innovation (cocos nucifera and moringa leaves) as an effort to prevent stunting in the Wanaraja Health Center work area, Garut Regency - Purwanto, Nofita Setiorini Futri; Ritonga, Siti Nurcahyani; Handayani, Titi Purwitasari (Science Midwifery, 2024)
Results of the 2022 Indonesian Nutritional Status Survey (SSGI), the stunting rate in Indonesia is 21.6%. West Java contributes to the stunting rate of 20.2% while the stunting rate in Garut Regency in 2022 (23.6%). The incidence of stunting in Wanaraja District, Wanamekar Village in February 2024 there were 100 stunted toddlers. Provision of safe and quality Supplementary Food (PMT) by paying attention to aspects of quality and food safety to improve nutrition in stunted toddlers. Provision of processed foods with local wisdom with CILOR innovation. This study aims to develop CILOR innovations in efforts to prevent stunting in the work area of ​​the Wanaraja Health Center, Garut Regency. Quasi Experiment Research Design with the One Group Pretest-Posttest design approach, One group of research subjects without a comparison group. The subjects of this study were children aged 24-59 months, subjects by quota sampling. The number of samples was 19 research subjects. Secondary data collection of observation sheets for 30 days, primary data of anthropometric measurements as much as 4 times The results of the study showed that after the intervention was given to the treatment subjects, an increase in the height of stunted toddlers was obtained by 0.2 to 1.6 cm. The normality test before being given PMT was 0.104> 0.05 and after the intervention was 0.177> 0.05. This shows that the data is normally distributed and the results are significant so that there is an influence of Cilor Innovation on the height of stunted toddlers in the Wanaraja Health Center work area.